Detection of increased intracranial pressure in trans‐oral robotic thyroidectomy using optic nerve sheath diameter measurement. Issue 2 (5th November 2022) - Lim, Hyunyoung; Kim, Eugene; Kim, Soo Yeon; Kim, Ji‐Yoon; Jung, Yundo; Lee, Tagkeun; Kim, Nayeon; Tae, Kyung
Abstract: Background: During transoral robot‐assisted thyroidectomy, there is a risk of increasing intracranial pressure because the site of CO2 insufflation is narrow and close to the brain. Methods: We analyzed the pre‐ to post‐CO2 neck insufflation change in the optic nerve sheath diameter during transoral robot‐assisted thyroidectomy. Changes in vital‐signs, airway pressure, and arterial carbon dioxide pressure were analyzed along with postoperative complications. Results: Among the 30 participants, the post‐CO2 inflation mean optic nerve sheath diameter (5.64 ± 0.54 mm) was higher than the pre‐induction diameter (4.81 ± 0.37 mm) with a mean difference of 0.83 (95% CI, 0.69–0.97; p < 0.001), but returned to baseline after CO2 deflation in most cases. One participant had sustained increased optic nerve sheath diameter (6.35 mm) associated with severe new‐onset postoperative headache. Conclusion: Transient elevation in the intracranial pressure during low‐pressure CO2 neck insufflation in the transoral robot‐assisted thyroidectomy did not appear to adversely affect patients.